PENDAPATAN DAN EFISIENSI TEKNIS USAHATANI UBI JALAR DI JAWA BARAT : PENDEKATAN STOCHASTIC FRONTIER - Khotimah, Husnul; Nurmalina, Rita (Forum Agribisnis, 2012)
Sweet potato is one of carbohydrat source to support the diversification food program. However, its productivity is still low and decreasing. It is caused by inefficiency in cultivation technique. The purposes of this research are to analyze farming revenue and to analyze factors affecting business and technical efficiency of sweet potato farming. Sampling method was conducted by proportional random sampling and the number of sample used was 30 people. The methods are revenue cost ration (R/C), break event point (BEP) and frontier production function estimated by MLE with Cobb-Douglas production function. The result shows cash revenue to cost ratio of 1.69 and total revenue to cost ratio of 1.23 which confirm the notion of efficient and lucrative. Price BEP is 772.60 rupiahs per kg and unit BEP is 15291.80 kg per hectare. The farming price and production are more than BEP which show profitability. Frontier production function shows all variables are significant and positive except N fertilizer. The results show farming efficiency index of 0.52 to 0.99 averaged on 0.75. One third respondents have efficiency index below 0.70. The results shows positive and significant correlation of farming experience, side job and land ownership to technical efficiency. Farmerâ age, education, revenue of non-farming activities and farming training/counseling have negative and non significant correlation.